Dampak Kebijakan Pembangunan Kawasan Industri Terhadap Kesejahteraan Warga Di Kecamatan Genuk - Dimas Widya Prasetya; Hartuti Purnaweni (Journal of Public Policy and Management Review, 2016)
The development of Genuk industrial area is the implementation of Semarang City policy aims to enhance the revenue of Semarang City. Genuk industrial area consists of three regions with 458 units companies. The purpose of this research was to evaluate the impact of industrial area development policy to the welfare of people at Genuk Subdistrict. This research use descriptive research design with qualitative approach. Primary data in this research is the result of interviews with Industry and Trade Department of Semarang, Social Department of Semarang, Environmental Agency of Semarang, Genuk Subdistrict Office, and peoples at Genuk Subdistrict. The evaluation was done by looking at the negative and positive impacts of the industrial area. To measure the people welfare, this research use the welfare dimensions such as income level, education level, and health level.The results of this research was every people in Genuk Subdistrict have not feeling the walfare after the industrial area development process, because the impact which more dominant is the negative impacts from the industrial area development policy. The income level of every people can be enhance with the wages according to the regional minimum wages. The industrial area managers dan Semarang City Government can mantain the health level of every people still good by conducting environmental and health remediation activities after the industrial development